As narrativas sobre as práticas jornalísticas no podcast Pauta Pública: procedimentos de controle e ações de resistência no discurso dos jornalistas - Dornelles, Vítor Tassinari (2023)
In a wider sense, we understand podcasting as the production and the asynchronous circulation of audio shows on the internet. Despite its connection with radio language, it is a recent and a rising phenomenon, wich has been increasingly appropriated by media outlets. An interesting point about these productions is the use of reporters as sources of information. Following these ideas, this work investigates the narratives about the news practices as a result of the interviews with reporters in the Pauta Pública podcast, produced by Agência Pública. Based on the contributions of authors such as Leal (2013) and Resende (2009), we understand journalism as a producer of narratives about the present time. The podcast analyzed in this work, by bringing journalists to talk about their news stories, builds narratives about the news practices. Our understanding of news practices is based on the work of Ryfe (2017) and Marocco (2021), for whom these practices are constituted by the actions of individuals based on a common sense about what jornalism is and what it is for. Some of these practices are central to the discursive formation and make journalism as we see it. In this way, they constitute control proceedings that limit and define the discourse (FOUCAULT, 2009). We made our analysis through the theoretical-methodological perspective of the Narrative Critical Analysis, proposed by Motta (2013). This look allowed us to see the media outlet, the journalists hosts and the interviewed reporters as narrators and characters. It was also possible to deconstruct and understand texts that reflect on the journalistic work. We conclude that the programs build audio narratives through interviews that can be seen as dialogic (LAGE, 2002). In this space, journalists constitute themselves as expert and testimonial sources who reports practices that reflect and strain the journalistic discursive control proceedings.